IMPROVING STUDENTS’ WRITING SKILL OF DESCRIPTIVE TEXT BY USING EXAMPLE NON-EXAMPLE STRATEGY AT GRADE X OF VOCATIONAL MADRASAH ALIYAH ADZQIA BELIMBING - puspa gundary; Aprizon Aprizon (AL-ISHLAH: Jurnal Pendidikan, 2019)
The purposes of this research were to find out whether example non-example strategy can improve the students’ writing skill on descriptive, and to find out what factors influence the improvement of the students’ writing skill in writing descriptive text. This research was Classroom Action Research. This research was conducted in two cycles, which each cycle had three meetings. It was conducted from August 1st until August 31th.The researcher gathered the data in each cycles from observation checklist, field notes, interviews, and writing test. After analyzing the data, the researcher found that Example non-example strategy was able to improve the students’ writing skill of descriptive text through the process of comprehending the students, and assisting the students while they were writing. As the results, the students could improve their writing skill which involved the improvement of mean score of writing indicators; vocabulary, content/ideas, and organization. Moreover, it could be seen from the improvement of their mean score of basic score (56), test I (h62.5), and test II (79.4). Furthermore, the factors that influence the improvement of the students’ writing skill involved materials, media, and learning strategy. To sum up, the implementation of Example non-example strategy in teaching writing of descriptive text could provide positive results on their writing skill